ضرورة تحديث علم الكلام ومستوياتُه - السالمي, ياسين (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2017)
يروم هذا البحث تأكيد أهمية علم الكلام، وضرورة تحديثه عن طريق جملة من المقترحات التي يُقدِّمها، اعتماداً على مراجعة مجموعة من المفاهيم المحورية، مثل: مفهوم أصول الدين، والتمييز بين مراتب مسائل علم الكلام، التي تتيح تحديث المواقف الرافضة لعلم الكلام، وتحديث موقف المتكلمين أنفسهم من الخلاف الكلامي. ويسعى هذا البحث إلى بيان مجالات التحديث التي يمكن أنْ يُشتغَل بها في تلك المراتب. This study emphasizes the importance of Islamic Theology and the need for its renewal, and the update of its levels through a number of suggestions, based on the review of a set of central concepts, with specific focus of the concept of foundations of the religion. The study tries to distinguish between ranks of theology which allows updating positions on theology rejection, update positions of theologians themselves on theology dispute, and explain areas of these ranks that deserve the renewal.